2008
DOI: 10.1128/jb.01847-07
|View full text |Cite
|
Sign up to set email alerts
|

The Global Responses of Mycobacterium tuberculosis to Physiological Levels of Copper

Abstract: Copper (Cu) is a required micronutrient, but it is highly toxic at high concentrations. Therefore, the levels of Cu must be tightly regulated in all living cells. The phagosome of Mycobacterium tuberculosis has been shown to have variable levels of Cu. Previously, we showed that M. tuberculosis contains a copper-sensitive operon, cso, that is induced during early infection in mice. In this study, we showed that ctpV, a gene in the cso operon, is a copper-responsive gene and most likely encodes an efflux pump f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
150
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(163 citation statements)
references
References 40 publications
13
150
0
Order By: Relevance
“…Microarray experiments in S. aureus SH1000 reveal that the expression of CsoR is not strongly induced by copper stress, unlike the situation in M. tuberculosis (13,50); as a result, constitutively expressed CsoR might play a role in buffering "free" Cu(I) in S. aureus in the Ϸ10 Ϫ18 M range. On the other hand, the gene encoding the likely copper chaperone CopZ just downstream from copA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Microarray experiments in S. aureus SH1000 reveal that the expression of CsoR is not strongly induced by copper stress, unlike the situation in M. tuberculosis (13,50); as a result, constitutively expressed CsoR might play a role in buffering "free" Cu(I) in S. aureus in the Ϸ10 Ϫ18 M range. On the other hand, the gene encoding the likely copper chaperone CopZ just downstream from copA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, quantitative RT-PCR experiments showed that mmcO transcription is increased by addition of copper (40) and is regulated by the copper-responsive RicR protein (41). To examine how MmcO protein levels changed in M. tuberculosis under copper stress, we utilized the avirulent M. tuberculosis strain mc 2 6230 and its isogenic ⌬mmcO mutant.…”
Section: Resultsmentioning
confidence: 99%
“…Before DNA microarray hybridizations, doublestranded cDNA was synthesized from 10 g of total RNA using the SuperScript Double-Stranded cDNA Synthesis Kit (Invitrogen), as directed by the manufacturer, in the presence of 250 ng genome-directed primers (41,49). The doublestranded cDNA was cleaned up and labeled following the NimbleGen gene expression analysis protocol (NimbleGen Systems, Inc., Madison, WI) and hybridized to NimbelGen-manufactured microarrays following a protocol we established earlier (49). In this microarray, each of the 3,989 open reading frames in the genome of M. tuberculosis strain H37Rv was represented by 19 probes of 60-mer oligonucleotides.…”
Section: Methodsmentioning
confidence: 99%